Carrier Frequency Offset Estimation in OFDM systems as a Quadratic Eigenvalue Problem - A. Eslahi; A. Mahmoudi; H. Kaabi (Radioengineering, 2017)
Carrier frequency offset (CFO) in orthogonal frequency division multiplexing (OFDM) systems is a major problem in achieving orthogonality between subcarriers. In this paper, we propose an estimator for CFO in OFDM systems using the subspace method. We used the linear prediction property of a complex sinusoidal signal. The estimator was obtained by solving a quadratic eigenvalue problem. Its performance was examined and compared with a Maximum-Likelihood (ML), Cyclic-Prefix based and Pilot-based estimators by the measures of mean square error (MSE), and Cramer-Rao Lower Bound (CRLB). Numerical results are presented to show the visible advantages obtained by using this estimator.